2012
DOI: 10.1038/pj.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

Giant single crystal of isotactic polypropylene showing near-equilibrium melting temperature

Abstract: Giant single crystals of isotactic polypropylene (iPP) were obtained using a specific kinetic pathway through the mesophase of iPP; the pre-quenched iPP mesophase was heated to 166 1C at a rate of 75 1C min À1 and maintained at this temperature for 24 h. The obtained crystallites exhibited a very high melting temperature, T m , of 183.7 1C, which is B19 1C higher than the iPP's nominal T m (B165 1C); namely, the observed T m is immediately close to the literature value of iPP's equilibrium melting temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…35 In addition, the melting temperature-annealing temperature line of isotactic polypropylene reported by Asakawa et al also showed the slope around 1. 36 However, the authors did not discuss this observation. 35,36 In contrast to our results, in the range of low T c , the melting point of the copolymer used by Kim et al did not increase much with increasing crystallization temperature.…”
Section: ■ Materials and Sample Preparationcontrasting
confidence: 99%
“…35 In addition, the melting temperature-annealing temperature line of isotactic polypropylene reported by Asakawa et al also showed the slope around 1. 36 However, the authors did not discuss this observation. 35,36 In contrast to our results, in the range of low T c , the melting point of the copolymer used by Kim et al did not increase much with increasing crystallization temperature.…”
Section: ■ Materials and Sample Preparationcontrasting
confidence: 99%
“…Asakawa et al took 24 h to obtain crystals with a melting temperature 183.7°C by crystallizing iPP at 166°C. 20 Our results suggest an effective approach to achieve iPP sample with ultrahigh melting temperature. The ultrahigh melting temperature means formation of thick lamellae or other unique crystalline architecture, which are undoubtedly attributed to the mutual effect of pressure and shear flow.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, the total melting enthalpy measured in the final melting step was ≈126 J g −1 , while exothermic 102 J g −1 was obtained in the first isothermal step conducted at 145 °C. Furthermore, the relatively large fraction of the polymer melting in the range 180–190 °C, obtained practically from an isothermal crystallization at a relatively low temperature of 145 °C points toward the possibility that the equilibrium melting temperature of iPP is often underestimated …”
Section: Resultsmentioning
confidence: 99%